Urban planning of the cities of the Yekaterinoslav Province in the era of modern times - Ольга Баева; Армен Казарян (Проект Байкал)
Taking as an example the largest cities, which were part of the Yekaterinoslav Province in the era of modern times, the article considers the features of the urban planning approach that prevailed during the reign of Catherine II. It presents the characteristics of the established centres and reveals the peculiarities of the formation of their historical core. It is noted that the majority of classicist cities of the region developed on the basis of the continuity principle and their historical structure. The authors highlight the special value of the central zone of these cities as a basis of the urban environment and the necessity of preservation of the historical centre or (in case of its loss) of the basic planning and spatial parameters.